Feasibility of Ecosystem Services Concept Implementation for Russian Cities - SULKARNAEVA, Liliia D. (Journal of Environmental Management and Tourism, 2019)
This article considers feasibility of ecosystem services assessment for Russian cities. The high significance of this study is determined by the assignment of the President of the Russian Federation to the Government of Russia to develop an action plan aimed at strengthening Russia's position for the formation of international environmental agenda and discussion of issues related to the creation of a system of compensation (payments) for ecosystem services, focusing at Russia’s position as an environmental donor (Pr-140GS, p.1 d, dated December 26, 2016), on the one hand, and implementation of the strategy for housing development for Russian Federation till 2015, on the other. In this paper, ecosystem services as both direct and indirect effects of ecosystems on the well-being of society are considered. The high relevance of the assessment of ecosystem and urban ecosystem services for Russian Federation is discussed. Adaptation of foreign methods for the Russian Federation is actualized. Various approaches to the classification of urban ecosystem services are considered, and a classification of urban environmental services for Russian cities is developed in accordance with Russian legislation. Foreign approaches for the assessment of the ecosystem service "Air Purification" are considered, and existing limitations for the application of these approaches in Russian cities are identified. Russian approaches for the regulation functions assessing of the urban ecosystems are analyzed: dust, gas purification by soils, urban green zones. Approaches for assessing of the need for the ecosystem service "Air Purification" in the city were analyzed. By the example of the "Air Purification" service determines the possibility of adapting approaches to the assessment of ecosystem services for Russian cities are shown.